Encounter Risk Analysis of Rainstorm and Tide Base on Different Sampling Method - WANG Shangwei; LIU Zengmei (Renmin Zhujiang)
Waterlogging disaster in tide-affected area usually occurs under the influence of rainstorm and tide level.In the process of risk analysis of rainstorm and tide level,different sample methods will affect the risk probability results.Taking Zhong-Zhu union catchment as an example,based on annual maximum series sampling method and peak over threshold sampling method combined with Copula function,the risk analysis results indicate that:①Sample data obtained based on peak over threshold sampling method has a larger sample size,which contains more rainstorm events than sample data obtained based on annual maximum series sampling method,and these rainstorm events tend to encounter high tide;②On the basis of containing more effective sample information,the frequency analysis results obtained by peak over threshold sampling method are more accurate and with much more security from the perspective of waterlogged drainage;③The joint distribution of rainstorm and tide based on peak over threshold sampling method showed a better fitting degree,and the probability of encountering unexpected events is larger as a result of annual maximal series sampling method omitted some effective sample information.